2012
DOI: 10.1136/annrheumdis-2012-202254
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and overweight determine the likelihood of developing rheumatoid arthritis

Abstract: ObjectivesRheumatoid arthritis (RA) is a prototypic chronic inflammatory disease with a debilitating course if untreated. A genetic predisposition for RA is known, and its occurrence is associated with the presence of autoantibodies in the serum and with environmental factors. It is unknown if smoking and overweight are contributory factors for developing RA in individuals with RA-specific autoantibodies in the serum.MethodsFifty-five individuals at risk for developing RA, based on the presence of RA-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(123 citation statements)
references
References 25 publications
4
113
2
4
Order By: Relevance
“…It is therefore difficult to speculate whether their modification would be sufficient to rescue a high risk phenotype where systemic autoimmunity is well established and clinical and/or imaging features have often already developed in the joints. A smoking history and elevated BMI were associated with an increased risk of arthritis development in seropositive at risk individuals in one small study [49]. This is in keeping with data from the US Nurses Health Studies, where elevated BMI was associated with seropositive and seronegative RA development [50].…”
Section: Towards Prevention: Management Of At Risk Individualssupporting
confidence: 77%
“…It is therefore difficult to speculate whether their modification would be sufficient to rescue a high risk phenotype where systemic autoimmunity is well established and clinical and/or imaging features have often already developed in the joints. A smoking history and elevated BMI were associated with an increased risk of arthritis development in seropositive at risk individuals in one small study [49]. This is in keeping with data from the US Nurses Health Studies, where elevated BMI was associated with seropositive and seronegative RA development [50].…”
Section: Towards Prevention: Management Of At Risk Individualssupporting
confidence: 77%
“…Smoking influences transitions between preclinical phases in the development of RA (27)(28)(29). Smoking may contribute to RA pathogenesis by interacting with the HLA-DRB1 shared epitope to increase RA risk, perhaps through the formation of citrullinated neoantigens, resulting in loss of tolerance, autoimmunity, and systemic inflammation, eventually resulting in polyarthritis (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…It is also found that nulliparity increases RA risk. Obesity is also an important risk factor for RA in western countries, as being overweight increases the levels of circulatory leptins and stimulates proinflammatory cytokines such as TNFα and interleukin-1 (20).…”
Section: Hormonal Factorsmentioning
confidence: 99%